A FUNÇÃO DO CUIDAR E EDUCAR NA EDUCAÇÃO INFANTIL EM TEMPOS DE PANDEMIA NO MUNICÍPIO DE PARANAGUÁ-PR (REMUNOM, 2023)
The aim of this paper was to understand how the process of experiencing Early Childhood Education remotely took place in the municipality of Paranaguá -PR, from the point of view of parents and teachers and what impacts this could have on the school process of these children.  The year 2020 saw the Coronavirus pandemic spread at an accelerated rate, and accompanied by restrictive measures to prevent the spread of the virus, the Ministry of Education decided to start remote classes at all levels and stages of education. Society experienced a unique moment and remote learning took over the homes of every student in the country. This change happened very quickly, so teachers had to adapt and adopt strategies to make the classes effective. Our discussion will focus on caring and educating, the function of early childhood education and the role of the teacher at this stage of education. In a way, this process was not carried out remotely by teachers, but by those who went through this period with the children.  We sought to address how remote teaching was in the pandemic in the general world context, in Brazil and specifically in the municipality of Paranaguá, what strategies the Municipal Department of Education adopted and how each Municipal Teaching Center was organized so that this moment occurred, seeking through field research, an answer to our problem.